Engaging young learners of English with multilingual digital storytelling (MDST) during covid-19 school closure - Nuroh , Ermawati Zulikhatin; Retnaningdyah , Pratiwi; Munir , Ahmad (JEES (Journal of English Educators Society), 2021)
The use of Multilingual Multimedia Storytelling (MDST) to teach English to primary school students is nothing new in Indonesia. However, digital learning is still not implemented in practice because English in primary schools is a local subject and a foreign language. In this research, the researchers used Multilingual Digital Storytelling (MDST) as a model for encouraging and reflecting on multiliteracy in education. They understand the importance of storytelling, and interactive storytelling has self-representation and communication with others. This research explicitly outlines our experience of using MDST as a pedagogical innovation for pupils aged 12 years. In this MDST project, students co-created digital stories as multimodal texts. In this regard, they used a variety of multilingual (e.g. Javanese, Bahasa Indonesia, and English) as well as visual and technical resources, which enabled them to communicate their real-life experience through digital stories. The practical consequences of the project are that English primary school teachers will experiment with MDST to involve students in effective project-based language learning. HIGHLIGHTS: The multilingual digital story (MDST) -making learning provided students with a new way to tell their ownstory in a multilingual way, and to share and explore their life experiences through the production of digitalstories2. Engaging students with multilingual digital stories, they have more creatively developed their stories basedon images taken by themselves.3. English primary school teachers will experiment with MDST to engage students in language learning as aneffective method of innovative learning.